2014
DOI: 10.1590/0103-8478cr20131426
|View full text |Cite
|
Sign up to set email alerts
|

Digestible energy of crude glycerol for pacu and silver catfish

Abstract: The increase in global biodiesel production is originating a glycerol surplus, which has no defi ned destination. An alternative to overcome this problem is its use as energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Glycerol has been proved to be a good alternative feed that can be used as source of energy for omnivorous fish (Li et al, 2010;Neu et al, 2013;Balen et al, 2014;Costa et al, 2015Costa et al, , 2017Moesch et al, 2016), in the meantime, the use of glycerol in the fattening stage of fish, as Nile tilapia, has not been sufficiently studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol has been proved to be a good alternative feed that can be used as source of energy for omnivorous fish (Li et al, 2010;Neu et al, 2013;Balen et al, 2014;Costa et al, 2015Costa et al, , 2017Moesch et al, 2016), in the meantime, the use of glycerol in the fattening stage of fish, as Nile tilapia, has not been sufficiently studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…The use of glycerol as an energy source in fish varies according to fish species and size (Neu et al, 2013), possibly due to the gastrointestinal tract formation and the composition of the product (Fernandes et al, 2016). It is a potential source of energy for Nile tilapia (Meurer et al, 2012; Neu et al, 2012b; Costa et al, 2015; Gonçalves et al, 2015; Meurer et al, 2016; Moesch et al, 2016; Santos et al, 2019), common carp (Fernandes et al, 2016), channel catfish (Li et al, 2010), jundiá, pacu (Balen et al, 2014) and curimbatá (Balen et al, 2017) (Table 3).…”
Section: Use Of Glycerol As An Energy Source In Fishmentioning
confidence: 99%
“…Crude glycerol displays adequate potential to be used in the substitution of other energetic ingredients in dietary fish formulation, due to a digestible energy of 13.09 MJ kg −1 for Nile tilapia juveniles (120 g) (Meurer et al, 2012), similar to maize (13.87 MJ kg −1 ) and wheat bran (13.08 MJ kg −1 ), and higher than maize starch (10.52 MJ kg −1 ), sorghum (11.62 MJ kg −1 ) and maize germ (9.00 MJ kg −1 ), also for Nile tilapia juveniles (100g) (Pezzato et al, 2002). For Piaractus mesopotamicus , crude glycerol comprises 15.20 MJ kg −1 of digestible energy (Balen et al, 2014), higher than maize (14.49 MJ kg −1 ), wheat bran (13, 86 MJ kg −1 ) and sorghum (14.52 MJ kg −1 ) and lower than rice bran (17.61 MJ kg −1 ) (Abimorad & Carneiro, 2004). For juvenile Rhamdia quelen , crude glycerol contains 13.95 MJ kg −1 of digestible energy (Balen et al, 2014), higher than the values reported by Oliveira Filho and Fracalossi (2006), of 9.62 MJ Kg −1 for maize and 10.28 MJ Kg −1 for rice chirera.…”
Section: Use Of Glycerol As An Energy Source In Fishmentioning
confidence: 99%
“…Crude glycerol derived from biodiesel presents great potential as a jundi a energy source, presenting an apparent digestibility coefficient of 0.89 and digestible energy content of 13.95 MJ kg À1 (Balen et al 2014). This may be related to the ease with which this nutrient is digested, absorbed and used.…”
Section: Apparent Digestibility Coefficientsmentioning
confidence: 99%